Pengaruh Kualitas Layanan, Citra Merek Dan Persepsi Harga Terhadap Minat Pembelian Ulang Pada Produk Golden Lamian - Jiddan, Muhammad Alem; Iskandar, Donant Alananto (STREAMING, 2024)
The purpose of this study is to ascertain whether service quality, brand image, and consumer perceptions of pricing, affect consumers' intentions to repurchase Golden Lamian goods. Consumers of these products who responded to a survey were asked for information. The link between the independent factors (brand image, pricing perception, and service quality) and the dependent variable (repurchase intention) was investigated using multiple linear regression analysis. The study's conclusions show that repurchase intention is highly influenced by pricing perception, brand image, and service quality. The management implications of these results can help businesses improve their customer service and marketing plans to win over more customers to Golden Lamian products.